Prominence Formation and Destruction. Issue Volume 8:Issue S300(2013) (6th January 2014) - Xia, Chun; Antolin, Patrick; Keppens, Rony
Abstract: In earlier work, we demonstrated the in-situ formation of a quiescent prominence in a sheared magnetic arcade by chromospheric evaporation and thermal instability in a multi-dimensional MHD model. Here, we improve our setup and reproduce the formation of a curtain-like prominence from first principles, while showing the coexistence of the growing, large-scale prominence with short-lived dynamic coronal rain in overlying loops. When the localized heating is gradually switched off, the central prominence expands laterally beyond the range of its self-created magnetic dips and falls down along the arched loops. The dipped loops recover their initially arched shape and the prominence plasma drains to the chromosphere completely.